Emerging Nurse Manager’s Resilience and Their Empowering Behavior during COVID-19 - Eman Salman Taie; Nessma Nehmedo Amine; Amira Fathy Akeel (Psych, 2022)
Background: The COVID-19 pandemic exacerbated tensions and tested the resiliency of many nursing leaders. Resilience enables head nurses to cope with their work environment challenges, and maintain healthy psychological activity. Moreover, their empowering behavior represents the vehicle to transform traumatic events such as the COVID-19 pandemic to create a high-quality work environment. Aim: To explore the relationship between nurse manager resilience and empowering leader behavior during COVID-19. Method: This is a descriptive correlational study. The study subjects consisted of two groups: head nurses (44) and staff nurses (284). The study was conducted at Benisuef University Hospital. Two tools were used for collecting data; nurse managers’ resilience scale, and staff nurses’ perceived empowering behavior during the COVID-19 pandemic via questionnaire. Results: In total, 50% of nurse managers had high resilience skills levels, about one-third of them (34.1%) had moderate levels and only 15.9% had low resilience skills levels. Furthermore, with regard to empowering leadership behavior levels as perceived by staff nurses during COVID-19; 66.9% of them perceived it high, 29.2% reported a moderate level of empowering behavior, and only 3.9% perceived low levels. Finally, there was a highly statistically significant positive correlation between nurse manager’s resilience skills levels and staff nurses’ perception of empowering behavior during COVID-19. Conclusions: Half of the nurse managers had high resilience skills, and only 15.9% had low levels. Two-thirds of staff nurses perceived high levels of their nurse manager’s empowering behavior during COVID-19, in comparison to only 3.9% who perceived low levels. There was a highly statistically significant positive correlation between nurse manager’s resilience skills levels and perceived empowering behavior during COVID-19.